2016
DOI: 10.2337/dc15-2800
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Diabetes and Hippocampal Atrophy in Elderly Japanese: The Hisayama Study

Abstract: OBJECTIVETo investigate the association between diabetes and brain or hippocampal atrophy in an elderly population. RESEARCH DESIGN AND METHODSA total of 1,238 community-dwelling Japanese subjects aged ‡65 years underwent brain MRI scans and a comprehensive health examination in 2012. Total brain volume (TBV), intracranial volume (ICV), and hippocampal volume (HV) were measured using MRI scans for each subject. We examined the associations between diabetes-related parameters and the ratios of TBV to ICV (an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
84
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(94 citation statements)
references
References 24 publications
8
84
2
Order By: Relevance
“…38 A similar pattern was seen in another study showing higher degrees of atrophy in older adults with DM2, particularly in those with longer diabetes duration and higher fasting glucose levels. 39 …”
Section: Geriatric Syndromessupporting
confidence: 78%
“…38 A similar pattern was seen in another study showing higher degrees of atrophy in older adults with DM2, particularly in those with longer diabetes duration and higher fasting glucose levels. 39 …”
Section: Geriatric Syndromessupporting
confidence: 78%
“…Finally, 141 articles were excluded because they were animal studies (n = 9), unable to provide information (n = 120) or without a full publication (n = 12). The remaining 12 studies were enrolled in the meta‐analysis . There were 4 prospective cohort studies, 6 cross‐sectional studies and 2 with both cohort and cross‐sectional data studies .…”
Section: Resultsmentioning
confidence: 99%
“…The remaining 12 studies were enrolled in the meta‐analysis . There were 4 prospective cohort studies, 6 cross‐sectional studies and 2 with both cohort and cross‐sectional data studies . For continuous HbA 1c , 4 cohort studies investigated different structural brain abnormalities: 2 involved white matter hyperintensities, 3 involved infarct, and 2 involved brain volume).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Possible underlying mechanisms of diabetes-related dementia include multifactorial pathways implicated in hyperglycemic toxicity, microvascular diseases, chronic inflammatory processes, and changes in insulin metabolism, which ultimately lead to small vessel infarcts, neuroinflammation, amyloid-β accumulation and neurodegeneration in the brain [2][3][4][5]. Conversely, obesity has also been implicated to play a role in the development of dementia in later life [6]; however, a recent study reported an inverse monotonic association between body mass index (BMI) and dementia incidence [7].…”
Section: Introductionmentioning
confidence: 99%